Plutarch and the New Testament in Their Religio-Philosophical Contexts : Bridging Discourses in the World of the Early Roman Empire - Hirsch-Luipold, Rainer, (Brill's Plutarch Studies ;, 2022)
How to read Plutarch in the context of New Testament studies? Almost 50 years after the seminal project on the topic led by Hans Dieter Betz, this volume elevates once again the issue's priority. Bridging discourses is a fitting description both of the religio-philosophical spirit of Plutarch, the Platonist philosopher and priest of Apollo at Delphi, and the task of bringing his writings into fruitful dialogue with the writings of the New Testament, Hellenistic Judaism, and Early Christianity. Taken together, these authors constitute the religious Platonism of the early imperial era. Contributions from the fields of New Testament, classics, philosophy, religious studies, and patristics explore various ways of how to establish these bridges.